Quality of string-hopper prepared from high and low amylose rice - Kemashalini, K.; Prasantha, B.D.R. (University of Jaffna, 2018)
Physico-chemical properties of rice flour obtained from high and low amylos varieties, BG 360 and AT 405, were tested in this study. Physical properties st moisture content, moisture evaporation and cohesiveness of string-hoppers pr€ from both rice flours were tested. Physico-chemical characteristics, such as a content (%), damaged starch (%), swelling power (g/g), water absorption ca (%) and sedimentation volume (ml) were tested for both high and low amylos flours. String-hopper prepared from high amylose rice flour showed lower moisture and cohesiveness than string-hopper prepared from low amylose nce flour. A content of rice flour showed strong negative Pearson's correlation (>-0.9) wi cohesiveness and moisture content of string-hopper. In contrast to that a content of rice flour showed strong positive Pearson's correlation (>0.9) with r moisture evaporation from string-hopper. In spite of damaged starch of rice showed positive correlation (0.9-0.8) with cohesiveness and moisture cont (string-hopper, damaged starch showed negative Pearson's correlation (>-0.9 rate of moisture evaporation from the string-hopper. String-hopper made from high amylose rice flour BG 360 undergoes early gradation than string-hopper made from low amylose (AT 405) rice flour. string-hoppers made from high amylose rice flour showed better physical textural properties than low amylose rice: flour. High amylose BG 360 rice flour more suitable for string-hopper production than low amylose (AT 405) rice flour.
Keywords: Amylose; Damaged starch; Ride flour; String-hopper